2004
DOI: 10.4049/jimmunol.173.11.6905
|View full text |Cite
|
Sign up to set email alerts
|

Human CD8+ T Cells Recognize the 60-kDa Cysteine-Rich Outer Membrane Protein fromChlamydia trachomatis

Abstract: The intracellular bacterial pathogen Chlamydia is sequestered from the host cell cytoplasm by remaining within an inclusion body during its replication cycle. Nevertheless, CD8+ T cells recognizing Chlamydia Ags in the context of MHC class I molecules are primed during infection. We have recently described derivation of Chlamydia-specific human CD8+ T cells by using infected dendritic cells as a surrogate system to reflect Chlamydia-specific CD8+ T cell responses in vivo. These CD8+ T cell clones recognize chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The localization of OmcBc in the host cell cytosol correlates well with its immunodominance in C. trachomatis-infected women (29), which is consistent with the concept that exposure of chlamydial proteins to the host cell cytosol is accompanied by increased immunogenicity (19,52,53). OmcBc is dominantly recognized by not only human antibodies (19) but also human CD4 ϩ (54) and CD8 ϩ T cells (21), indicating that OmcBc can access multiple immune processing compartments (55). These observations suggest that OmcB is a highly dynamic molecule and that release of OmcBc into the host cell cytosol may allow OmcB to participate in both the chlamydial intracellular interaction with host cells and chlamydial modulation of host immune responses.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The localization of OmcBc in the host cell cytosol correlates well with its immunodominance in C. trachomatis-infected women (29), which is consistent with the concept that exposure of chlamydial proteins to the host cell cytosol is accompanied by increased immunogenicity (19,52,53). OmcBc is dominantly recognized by not only human antibodies (19) but also human CD4 ϩ (54) and CD8 ϩ T cells (21), indicating that OmcBc can access multiple immune processing compartments (55). These observations suggest that OmcB is a highly dynamic molecule and that release of OmcBc into the host cell cytosol may allow OmcB to participate in both the chlamydial intracellular interaction with host cells and chlamydial modulation of host immune responses.…”
Section: Discussionsupporting
confidence: 63%
“…We have confirmed that OmcB, a chlamydial outer membraneassociated, highly conserved, abundant and immunogenic protein (12,(18)(19)(20)(21)(25)(26)(27)(28), is processed during chlamydial infection since the processing was still detectable after the infected culture samples were harvested in 8 M urea, which has been shown to prevent proteolysis during cell lysis (30). Although we have previously reported that OmcB is partially cleaved (29), careful confirmation of OmcB processing in the current study is still necessary since a recent study has revealed that almost all previously reported protein cleavages in Chlamydia-infected cell samples are due to proteolysis during cell lysis (30).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…CTL have been used to identify antigens, such as major histocompatibility complex (MHC) class I-accessible protein 1, which were not detected by other techniques (11). In humans, C. trachomatis-specific CTL have been identified in subjects exposed to chlamydial infection (12,13,17,19,20). In these and other studies, CTL generated to a number of C. trachomatis epitopes that were restricted by common and disease-associated HLA types were used to identify peptide-specific responses (12,15,24).…”
mentioning
confidence: 99%